PROFESSIONAL & POLICIES - Aziz, Farida (Journal of Ayub Medical College Abbottabad, 2002)
Doctors dedicate their lives for learning, caring of patients and if they are in teaching, education of others. It is a continuous on-going and life-long process. But at the end of the day a doctor may think, have the things gone on as he or she wanted. We all criticise and discuss things many a time with a tinge of frustration. Frustration arises when things are not happening, as they should within the setup and within the resources. And a great feeling of satisfaction arises when things can be done or are being done with a desired standard within the resources and setup. Yet why is it that we do not often get this feeling of reward or satisfaction? It is because most of the time we subject ourselves to just a routine, set out for us. We lift our ideas and suppress them ourselves. I am sure if our individual self-guidance and thought process is regulated and then peer collected - and counseled - we will reach the ultimate goal of satisfaction and better student education and health care. Self-regulation is the key to improve standards - and then teamwork leads to policy making. The stress in health care & education has to be on awareness of disease pattern in this country, community education and prevention of disease. Thus the integration of educational system and politicians becomes an essential matter. But as such we the health professionals, everyone a dedicated expert in ones own field, are in a position to think about and choose people who should council matter of policies and health care - when we are guiding ourselves throughout our careers we are guiding health care - and that in itself becomes a policy - and perhaps the best policy. Because we have all seen the ups and downs and ins and outs of the society and the system. I think we should congratulate ourselves about our self-guided career tenures and do not hesitate to make honest policies out of them.